Reciprocal fraction function tools used for \-rung Quadripartitioned neutrosophic sets - M.Palanikumar; Nasreen Kausar; Dina Said (Neutrosophic Sets and Systems)
This paper presents a new method for creating a \-rung reciprocal fraction function. We introduce quadripartitioned neutrosophic sets (QNSS). The reciprocal fraction function applied to quadripartitioned neutrosophic sets are the neutrosophic sets and \-rung neutrosophic sets. This article will examine weighted geometric, quadripartitioned neutrosophic set weighted averaging, generalized weighted averaging, and generalized weighted geometric operators. Boundedness, idempotency, monotonicity and commutativity are also discussed.